Be nice to the air: Severe haze pollution and mutual fund risk - Surva R; Nguyen H; Visaltanachoti N (Elsevier Inc, 2023)
Motivated by the significant impacts of environmental risks on economic decisions and the increasing roles of mutual funds in financial markets in recent decades, this study examines the impact of ambient pollution on mutual funds’ risk outcomes. Using propriety data manually collected from several datasets, our fund fixed-effect regression estimates show that polluted air increases tracking errors and mutual fund return volatility. The adoption of different identification strategies, including instrumental variable estimations and difference-in-difference analyses based on two natural experiments, suggests the impact of air pollution on mutual funds’ risk is causal. Our findings suggest that air pollution harms fund managers’ cognitive abilities and impairs their investment efficiency, leading to an increase in mutual funds’ tracking errors and return volatility. Overall, our findings provide more insights into the impact of climate change on social behavior by shedding new light on the impact of air quality on asset managers’ behavior.
Keywords: Air pollution; Cognitive biases; Health concerns; Natural experiments; Tracking error; Return volatility